1, 4‐Dioxane Soil Remediation Using Enhanced Soil Vapor Extraction: I. Field Demonstration. Issue 2 (11th January 2018) - Hinchee, Robert E.; Dahlen, Paul R.; Johnson, Paul C.; Burris, David R.
Abstract: 1, 4‐Dioxane is totally miscible in water, sequestering in vadose pore water that can serve as a source of long‐term groundwater contamination. Although some 1, 4‐dioxane is removed by conventional soil vapor extraction (SVE), remediation is typically inefficient. SVE efficiency is hindered by low Henry's Law constants at ambient temperature and redistribution to vadose pore water if SVE wells pull 1, 4‐dioxane vapors across previously clean soil. It was hypothesized that heated air injection and more focused SVE extraction ("Enhanced SVE" or XSVE) could increase the efficiency of 1, 4‐dioxane vadose treatment, and this new process was tested at former McClellan Air Force Base, CA. The XSVE system had four peripheral heated air injection wells surrounding a 6.1 m × 6.1 m × 9.1 m deep treatment zone with a central vapor extraction well. After 14 months of operation, soil temperatures reached as high as ~90 °C near the injection wells and the treatment zone was flushed with ~20, 000 pore volumes of injected air. Post‐treatment sampling results showed reductions of ~94% in 1, 4‐dioxane and ~45% in soil moisture. Given the simplicity of the remediation system components and the promising demonstration test results, XSVE has the potential to be a cost‐effective remediation option for vadose zone soil containing 1, 4‐dioxane.